G240(P) Severe head injury under 18 year olds – causes and outcomes over a 2 year period. (27th April 2016) - Fox, A; Doyle, J; Duffy, A; O'Toole, D; Houlihan, P; Caird, J; Nicholson, A
Abstract : Aims: We reviewed severe head injuries in children and adolescents who were treated in two national neurosurgical centres in 2013 and 2014. We studied the epidemiology, severity, care processes and clinical outcomes of these injuries. Methods: The TARN (Trauma Audit and Research Network) database was used to collect data for admissions of 72 h or greater from two national neurosurgical centres. Results: 117 patients with a severe head injury were admitted with a gender breakdown of 83 males and 34 females (2.4:1). 82 (61%) patients were transferred from another hospital. 64 (54%) of all head injuries were as a result of a fall, of which 45 (38%) were from less than 2 metres. Falls from less than 2 metres accounted for 27 (71%) injuries to children less than 2 years of age. Of 26 head injuries under 12 months of age, 5 (19%) were felt to be non-accidental injuries. There was a significant gender bias for mechanism of injury with 22 males and 8 females as a result of a vehicle collision (1.3:1) and 19 males and 1 female suffering a blow (19:1). The degree of head injury was scored using ISS (Injury Severity Score) and GCS (Glasgow Coma Scale). These showed that 85 (73%) had an ISS over 15, 19 (16%) between 9–15 and 13 (11%) between 1–8. 16 patients had a GCS under 8. The overall mortality was 5%. Morbidity was significant in that 21 survivors (18.9%) required intubation and 40 (34.1%) required one or more neurosurgical procedures. 21 (19%) patients had neuro-disability post-discharge all of which had an ISS > 15. Conclusion: In our cohort, falls were the most common cause of severe head injury. The mortality in our cohort was 5% reflecting the experience in tertiary neurosurgical centres. The large burden of care that these injuries place on the hospital system is evident by the high number of neurosurgical interventions. It is evident that ISS is a good prognostic indicator as all those with neuro-disability scored greater than 15. In infants, non-accidental injury should always be considered.